Genetic Diversity, Phylogenetic Tree and Principal Component Analysis Based on Morpho-Metric Traits of Assam Chilli - Prabalee Sarmah; Debojit Sarma; Sailen Gogoi (Journal of Plant Genetics and Crop Research, 2018)
We evaluated a set of 37 chilli genotypes collected and maintained at Assam Agricultural University, Jorhat for 27 different traits related to plant habit (5), leaf (6), flower (2), fruit (13) and biotic stress (1). The variation in fruit yield among the genotypes could be attributed to high coefficients of variability for component traits viz., number of fruits per plant (91.7%), plant height (80.8%), leaf breadth (55.9 %), fruit weight (49.7%), leaf length (45.4%) fruit length (35.8%), fruit breadth (35.5%) and number of branches per plant (22.2%). Maximum phenotypic variants were observed for fruit traits followed by leaf characteristics. Phylogenetic analysis revealed Euclidean distances varying from a minimum of 2.065 and a maximum of 13.311 indicating the diverse nature of the genotypes. UPGMA clustering grouped the genotypes into 5 distinct clusters. The largest one, cluster I, had 26 genotypes belonging to Capsicum annuum var. acuminatum. Cluster II consisted of Capsicum annuum var. conoides with cone-shaped fruits. Cluster III included Moni Jolokia, a perennial shrub with cone-shaped globose erect fruits which clustered in between the other local C. annuum sp. Bireek and Mem Jolokia. The fourth cluster (IV) included the local chilli genotypes - Mem Jolokia, Bhekuri Jolokia and Haitha Jolokia which were perennial, with green stem and leaves. Cluster V included the C. chinense genotypes consisting of Manipuri Bhut, Bor Bhut and Lota Bhut. The first principal component explained 34.93% of the total variation contributed by mostly leaf and fruit characteristics. The fruit characters in this component showed significant positive correlation with leaf length, breadth and plant height indicating their importance in the morphological characterization of the chilli genotypes.
Keywords: Capsicum annuum